PEG-6000 Induced Precipitation of Proteins from Cold-Acclimated Tenebrio molitor larvae - Gulevsky, Aleksandr K.; Grischenkova, Elena O.; Relina, Liana I.; Tretyak, Diana V. (Problems of Cryobiology and Cryomedicine, 2015)
Spectra of PEG-6000-precipitated proteins from cold-acclimated and non-acclimated Tenebrio molitor larvae were comparatively studied. The composition of precipitated proteins from cold-acclimated and non-acclimated T. molitor larvae was shown as differed qualitatively. In particular, the protein spectra of filtrates from cold-acclimated larvae had proteins with molecular weight of 11 kDa, which were absent in non-acclimated insects. There was observed a significant difference in precipitate content at polyethyleneglycol concentrations of 12% and higher during protein precipitation from homogenates of cold-acclimated and non-acclimated larvae. Proteins from the filtrates of cold-acclimated larvae in the presence of 6% PEG-6000 were precipitated by 44 and 56% greater, than those from non-acclimated species at 22 and 4Â°C, respectively. The increasing of PEG-6000 concentration from 4 to 6% resulted in appearance in the precipitates from cold-acclimated larvae of proteins with molecular-weight range of 30â€“42.5 kDa, which were absent in non-acclimated insects. Probl Cryobiol Cryomed 2015; 25(4):350-358.